PRODUKSI BAWANG MERAH DENGAN PEMBERIAN PUPUK KANDANG AYAM DAN KCL SEBAGAI SUMBER HARA - Fitri, Della; Armaini, Armaini; Islan, Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims is to determine the increase of onion production by giving chicken manure and KCl as a source of nutrients and to find out the combinations of chicken manure and KCl fertilizer is the best to increase the production of onion. The experiment was conducted in the experimental station of Faculty of Agriculture, University of Riau Campus Bina Widya Km 12,5 Simpang Baru Village Tampan Sub District Pekanbaru. This research was conducted from February to May 2017. This study used Completely Randomized Design (RAL) which consists of 2 factors. The first factor is the application of chicken manure (P) which are without chicken manure, 10 ton/ha and 20 ton/ha. The second factor is the application of KCl (K) fertilizer which are without KCl fertilizer, 200 Kg/ha, 300 Kg/ha and 400 Kg/ha. Parameters observed were the number of leaf per clumps, number of tubers per clumps, tuber perimeter, fresh tuber weight per plot, weight of worth saving tuber per plot, dry weight per clumps, production efficiency based on K fertilizer. The data obtained were analyzed statistically with variance and continued with Duncan's New Multiple Range Test (DNMRT) at 5%. The results showed that the interaction of chicken manure and KCl fertilizer can improve all observation parameters, to obtain growth and production of onion crops can be given the treatment of chicken manure dose of 20 ton/ha and treatment of KCl fertilizer dose of 300 kg/ha.Keywords: onion, chicken manure, KCl fertilizer